2020
DOI: 10.1002/cne.24975
|View full text |Cite
|
Sign up to set email alerts
|

Efferent projections of Vglut2, Foxp2, and Pdyn parabrachial neurons in mice

Abstract: The parabrachial nucleus (PB) is a complex structure located at the junction of the midbrain and hindbrain. Its neurons have diverse genetic profiles and influence a variety of homeostatic functions. While its cytoarchitecture and overall efferent projections are known, we lack comprehensive information on the projection patterns of specific neuronal subtypes in the PB. In this study, we compared the projection patterns of glutamatergic neurons here with a subpopulation expressing the transcription factor Foxp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 117 publications
(265 reference statements)
10
67
0
Order By: Relevance
“…To plot Syp-mCherry-labeled boutons for illustrations from case 1803 (Figure 12), we used an updated version of the custom algorithm we described in a recent publication (Huang et al, 2020)…”
Section: Imaging Figures and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To plot Syp-mCherry-labeled boutons for illustrations from case 1803 (Figure 12), we used an updated version of the custom algorithm we described in a recent publication (Huang et al, 2020)…”
Section: Imaging Figures and Analysismentioning
confidence: 99%
“…Previous tracing and lesion studies identified projections from the PB or KF to targets in the hindbrain and spinal cord (Fulwiler & Saper, 1984;Geerling et al, 2017;Herbert et al, 1990;Huang et al, 2020;Y. Q. Li et al, 1993;Saper & Loewy, 1980;Takada et al, 1984;Takeuchi et al, 1980;Travers & Norgren, 1983;Yoshida et al, 1997) (Hattox et al, 2002;Travers & Norgren, 1983).…”
Section: Comparison With Previous Neuroanatomical Tracing Studiesmentioning
confidence: 99%
“…were enriched, but Calca and Pdyn, markers for the external lateral and dorsal lateral parabrachial nucleus, were not (38,39). Notably, the PBL Oprm1 active transcriptome revealed several GPCRs expressed at high levels in these neurons, which we subsequently investigated as potential pharmacological targets to rescue OIRD.…”
Section: Resultsmentioning
confidence: 98%
“…In our view, OIRD is a synergistic outcome from impairment of the interconnected pontomedullary breathing network that widely expresses MOR both pre-and post-synaptically (10,11,30,44,45). For example, parabrachial neurons send tonic excitatory inputs to the preBötC (39,43,46,47), and both of these areas express MOR (18,48).…”
Section: Investigating Oird With Cell-type-specific Approachesmentioning
confidence: 91%
“…This discrepancy can be explained by the differences in optogenetic stimulation protocols. Whereas we used a 40-Hz light stimulation for 10 s as described 24 , Bowen et al used a 30 Hz light train for only 2 s. Moreover, it is worth noting that axonal bundles from all glutamatergic neurons in the PBel that project to forebrain regions, including the CeA, BNST, and PSTN pass through the VPMpc 84 , which suggests that optogenetic stimulation within the VPMpc activates both CGRP PBel axonal terminals and axon bundles passing through this area. Therefore, an alternative explanation of their observation is that concurrent stimulation of all downstream areas produces stronger aversive memory than stimulating CeA alone.…”
Section: Cgrp Neurons Convey Multisensory Innate Threat Cues To the Amentioning
confidence: 99%